The Influence of Father Involvement on the Academic Self-Efficacy of Tenth-Grade Students at SMAN Jatinangor in the 2024–2025 Academic Year - Rachmaniar, Ananda; Alfaiz, Alfaiz; Priatini, Gina Anggraeni (International Journal of Ethno-Sciences and Education Research, 2025)
This study aims to determine the influence of father involvement on the academic self-efficacy of 10th grade students at SMAN Jatinangor in the 2024–2025 academic year. The background of the study is based on the importance of the father's role in supporting the development of a child's self-belief in the academic context. This research employed a quantitative approach using a simple linear regression method. The sample consisted of 238 students selected based on specific criteria, namely those who live with both their biological father and mother. The instruments used included a father involvement questionnaire based on Hawkins et al. (2002) and an academic self-efficacy questionnaire based on Bandura’s theory (1997). The results showed that both father involvement and students' academic self-efficacy were in the moderate category. The regression test produced a significance value of 0.000 (<0.05) and a coefficient of determination (R Square) of 0.158. This indicates that father involvement contributes 15.8% to students’ academic self-efficacy, while the remaining percentage is influenced by other factors. Thus, it can be concluded that there is a significant influence of father involvement on students’ academic self-efficacy. This research has implications for parents, educators, and schools to enhance father involvement as an essential factor in supporting children's academic success